Indonesia Sharia Stock Investment During Covid-19: Based on Islamic Economic Law Review - Heradhyaksa, Bagas; Oktaviani, Rahma; Syukur, Suparman; Berlian, Hangrengga; Wahyudi, Ahmad (Jurnal IUS Kajian Hukum dan Keadilan, 2023)
The development of technology and financial literacy has increased the number of Indonesians who use stocks as an investment instrument. This also has an impact on the popularity of Islamic stocks. This is because many people are interested in Islamic investment instruments. However, the COVID-19 pandemic has had a significant impact on stock price movements. Sharia stock prices have also experienced very volatile movements due to the COVID-19 pandemic. This phenomenon raises the question of whether investing in Islamic stocks during the COVID-19 pandemic is against Islamic economic law. This is because Islamic stock prices seem to be filled with uncertainty and have experienced a very significant price decline. Moreover, due to the COVID-19 pandemic, the number of stock investors is increasing rapidly. This article aims to analyze Islamic stock investment during the COVID-19 pandemic through the perspective of Islamic economic law. To analyze this issue, this article collects data through library research. The data were analyzed using qualitative methods. In the end, this article finds that investing in Islamic stocks during the COVID-19 pandemic does not contradict the principles of Islamic economic law. Instead, this article suggests that the public can take advantage of a certain momentum to start investing in Islamic stocks.